Determination of Dexamethasone in Unregistered Herbal Weight Gain Using HPTLC-Densitometry - Asra, Ridho; Zulharmita; Yuliatim, Nopitri (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
A method was described for the simultaneous determination of dexamethasone in herbal weight gain. Three unregistered herbal weight gains (sample A, B, and C) were analyzed by using HPTLC-densitometry method. Samples were extracted as bases into methanol, separated by HPTLC silica gel 60 F254plate using chloroform: methanol (9:1) as mobile phase followed by densitometry measurement of its spot. The result showed that the detector response was linear for concentrations between 100-500 mg/mL (r =0.998). The limits of detection and quantitation were 9.19 mg/mL and 30.64 mg/mL, respectively. Dexamethasone contents from samples were analyzed. The result showed that two samples (sample A and B) were positively containing dexamethasone and the other one showed a negative result. The average contents of dexamethasone from both samples were 0.23% and 0.25%, respectively.